Redução de danos e gênero: a perspectiva de mulheres atendidas em um centro de atenção psicossocial alcool e drogas (CAPS AD) - Lazarini, Emily (Universidade Federal de São Carlos, 2025)
The use of psychoactive substances (PAS) is a phenomenon of interest throughout the development of the human species. From the 16th century onwards, the abusive use of these substances became a topic of interest, relating to social determinants of health (SDH), among them, the construct of gender. This research investigated women's representations of themselves while in a condition of abusive PAS use. This was a qualitative, interpretative and descriptive empirical research, belonging to the epistemological framework of critical and interpretative social psychology called hermeneutics-dialectics. The invited participants consisted of 7 women attended at a Psychosocial Care Center for Alcohol and Drugs (CAPS AD III) in the city of São Carlos. The instrument for data production was a semi-structured interview guide, composed of 2 parts: a socioeconomic questionnaire; and a semi-structured part that guided the interview. The questions in the guide aimed to characterize the participants and investigate their history of substance use, the relationships between being a woman and being a substance user, and the history of treatment at the CAPS (Psychosocial Care Center). Data analysis was performed using Thematic Analysis, and the discussion of the results was based on the articulation of this data. This investigation can contribute to adding information about harm reduction and its relationship with gender and public policies, considering the few available studies that evaluate this relationship.
Harm reduction and gender: the perspective of women treated at a psychosocial care center for alcohol and drugs (CAPS AD)
Keywords: Redução de danos; Saúde mental; Gênero; Políticas públicas; Teoria das representações sociais; CIENCIAS HUMANAS::PSICOLOGIA::PSICOLOGIA SOCIAL::RELACOES INTERPESSOAIS; 5. Igualdade de Gênero